Partisipasi Masyarakat dalam Penguatan Pendidikan Karakter Peserta didik SDN 24 Macanang Kabupaten Bone - Aras, Astina; Mustami, Muh Khalifah; Rapi, Muh (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2020)
Schools need to realize character education as the goal of national education. This study aims to determine the realization of community participation in strengthening character education. This research is a descriptive qualitative study using a phenomenological, management and sideological approach. Data collection techniques using observation, interviews, and documentation. Data processing and analysis techniques through data reduction, data presentation, and verification or conclusion drawing. The validity test of this research data includes the test of credibility of data, transferability, dependability and confirmability. The results of this study indicate that community participation in strengthening character education is channeled through school committees that give birth to operational policies and educational programs in schools, provide assistance in the form of voluntary funds, material contributions and involve themselves in carrying out activities to strengthen character education both class-based, culture-based and community based.